Current Orofacial Pain: An Updated Data for Physicians, Pharmacists, Nurses, Pathologists, Dentists, Physical Therapists, and Respiratory Specialists - Al-Ahmari, Mohammed Saad Mohammed; AL AHMARI, ABDULRHMAN MUSHBAB OUDAH; Alshahrani, naser Ayed naser; albalwi, Sami hamowed ahmad; ALBalawy, Mary Awid; Mitwalli , Jawaher Saleh; Thabit, Razan Khalid; Alshehri, Mazen Shar mohi; Alammary, Khaled Salem; Aljubran , Ali Saleh; Mansaki, Hassan Hussain Mohammed; Badawood, Ahmed Omar; et al. (Journal of Ecohumanism, 2024)
Background: Orofacial pain is a prevalent health issue that significantly impacts patients’ quality of life. It encompasses a wide range of conditions, including dental pain, musculoskeletal disorders, and neuropathic pain, each requiring distinct diagnostic and therapeutic approaches. Despite advancements in pain research, managing orofacial pain remains challenging due to its complex etiology and the lack of standardized diagnostic criteria. Aim: This review aims to provide an updated overview of orofacial pain, focusing on its classification, underlying mechanisms, and management strategies. It emphasizes the importance of accurate diagnosis, particularly in differentiating between neuropathic and odontogenic pain, and highlights the roles of various healthcare professionals in managing this condition. Methods: The review synthesizes current literature on orofacial pain, including its definitions, classifications, and treatment modalities. It discusses the International Classification of Orofacial Pain (ICOP), pharmacological and non-pharmacological interventions, and the roles of multidisciplinary teams in pain management. Results: Orofacial pain is classified into nociceptive, neuropathic, and nociplastic categories, each requiring tailored treatment approaches. Neuropathic pain, in particular, poses diagnostic challenges due to its subjective nature and lack of definitive criteria. Effective management often involves a combination of pharmacological treatments (e.g., anticonvulsants, antidepressants) and non-pharmacological interventions (e.g., hypnosis, acupuncture, manual therapy). Collaborative care involving dentists, neurologists, nurses, physical therapists, and respiratory specialists is essential for optimal outcomes. Conclusion: Orofacial pain is a multifaceted condition that requires a comprehensive, multidisciplinary approach for effective management. Accurate diagnosis, patient education, and the integration of pharmacological and non-pharmacological therapies are crucial for improving patient outcomes. Future research should focus on refining diagnostic criteria and exploring innovative treatment modalities to address the complexities of orofacial pain.